(untitled) (Comprehensive Journal of Science, 2026)
This research examines the military conflict between Caliph Abd al-Rahman al-Nasir li-Din Allah (300-350 AH/912-961 AD) and the Christian emirates of León, Navarre, and Castile that emerged in northern Al-Andalus as a result of the Gothic secession following the defeat of the Goths by the Muslim conquerors in the Battle of Shduna in 92 AH/711 AD, in an introduction, two chapters, and a conclusion. The first chapter presents the historical framework for the emergence and development of these emirates from fragile pockets of resistance into expansionist entities during the era of the Emirate. It clarifies the position of their kings regarding Abd al-Rahman al-Nasir li-Din Allah’s accession to the throne of Al-Andalus and discusses their initial military confrontations with him. The second chapter argues al-Nasir’s policy in managing the military conflict with these principalities, presenting the most significant incursions he launched against León, Navarre, and Castile under this policy, analyzing the motivations behind these incursions, and evaluating their outcomes for both sides.